Ecofriendly Dyeing of Textiles with Natural Dyes Extracted from Commercial Food Processing Waste Materials. Issue 15 (23rd November 2022) - Amutha, K.; Annapoorani, S. Grace; Sakthivel, P.; Sudhapriya, N.
ABSTRACT: Textile wet processing industry is one of the dreadful polluters in the world. An alternative to hazardous synthetic dyes could be dyes derived from various natural sources such as plants, insects, and minerals. Additionally, agro-waste and food processing waste could serve as effective sources of natural dyes. The current study focuses on extraction of natural dyes from two commercial food processing waste materials, namely, the spent coffee grounds and the roasted peanut skin. The dyes were found to possess rich tannin content and were applied on silk, cotton, and nylon fabrics with and without the aid of mordants using water bath and ultrasonic bath. The dye exhaustion percentage is better in water bath dyeing for spent coffee grounds dye while its vice versa for the roasted peanut skin dye. Both the dyes show good color fastness to washing with silk and nylon fabrics while the grades are poor in case of cotton. However, the myrobalan and alum mordanted cotton fabrics exhibit very good color fastness to laundering. The color fastness to light is below average as is the case with most natural dyes. The spent coffee grounds dye give yellow to light brown shades while the roasted peanut skin dye give pink shades on cotton, silk, and nylon fabrics. With the use of ferrous sulfate mordant the dyes give different shades of gray color.